PENDAMPINGAN BRANDING VISUAL DAN PERHITUNGAN HARGA POKOK PRODUKSI (HPP) UNTUK MENINGKATKAN DAYA SAING UMKM PEYEK DAN BAGOR BU MARTIN - Winarti Kusuma Dewi; M. Solahuddin; Adam Ferdiansyah; Falihul Azam; Dian Anita Sari (Fokus ABDIMAS, 2026)
Bu Martin’s Peyek and Bagor MSME is an MSME that was established in 2012. According to the results of a preliminary survey, in running their business, the MSME faces challenges in the areas of promotion, product identity, and financial management, specifically in calculating the cost of goods sold (COGS). Based on observations, the community service activities were conducted with the aim of helping to enhance marketing appeal and providing business owners with an understanding of how to calculate COGS in relation to business profits. The implementation methods included observation, interviews, mentoring, and the direct execution of the work program at the business location of Bu Martin’s Peyek and Bagor SME. The work program included creating business banners, compiling product price catalogs, designing packaging stickers, and calculating COGS. The results of the activities for the Peyek and Bagor Bu Martin SMEs were that the SMEs now have more attractive promotional materials in the form of banners, product stickers, and product catalogs. Additionally, the business owner has gained a better understanding of how to determine selling prices based on COGS, allowing for more accurate calculations of business profits. Through this initiative, it is hoped that Bu Martin’s Peyek and Bagor SME can enhance its competitiveness and support sustainable business development.